The Shariah governance practices and Islamic banks performance in Malaysia - Naysary, Babak (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2018)
Despite the extensive research on the significance of corporate governance in firms and its well-established relationship with performance and also its role in the recent financial crisis, there is still a gap in the literature in terms of highlighting the practical aspects of Shariah governance in IFIs and also translating its functions into actual performance. In order to fill this gap, this research was an attempt to first, evaluate the impact of Shariah Governance Framework-2010 (SGF-2010) on improving the Shariah governance practices and addressing its issues; then look into the two aspects of overall performance namely efficiency and effectiveness and examine any significant change before and after enforcement of SGF-2010 and finally investigate impact of Shariah governance practices on the performance of Islamic banks in Malaysia. In order to fulfill these objectives, a questionnaire was developed based on the items in SGF-2010. In order to evaluate any improvements before and after the regulations a comparative analysis was done based on questionnaire scores. For the purpose of performance measurement, quantitative analysis focused on DEA to examine the efficiency of Islamic banks and CAMEL rating to measure their effectiveness. T-test was run to investigate any changes in these two performance measures. Additionally, Pearson's correlation analysis was used to check the consistency between these measures. Finally, to fulfill the last research objective through qualitative analysis, 11 interviews was conducted with Shariah governance key players to investigate the practical implications of Shariah governance on actual performance. The findings achieved in this research suggest that BNM regulations particularly SGF-2010 have significantly improved the Shariah governance practices in Islamic banks in Malaysia. The results of performance analysis indicated a significant change in efficiency of all Islamic banks after SGF-2010 which signifies the impact of regulations in banking efficiency. However, the results did not support any significant change in the effectiveness of Islamic banks as measured by CAMEL scores. Finally, the results of interview with industry practitioners suggest that all five components of Shariah governance can significantly impact the performance of Islamic banks. The findings of present research provide insight for regulatory bodies in terms of the impact of regulations on Shariah governance practices. Performance measurement results provides Islamic banking practitioners with the opportunity to review and compare their performance and to determine the causes of their success and failure to achieve excellence. The research findings augment the extant literature through theoretical development new methodology.